Run, swim, throw, cheat: The science behind drugs in sport - Cooper, C. (Oxford University Press, 2012)
This book - looks at the performance of top athletes and considers the limitations of human performance - explains how drugs work and the challenges of testing for them - considers recent research with rats and mice to study physical limitations and - raises ethical questions for the future of sport and improving human performance. Drugs in sport are big news and the use of performance-enhancing drugs in sport is common. Here, Chris Cooper, a top biochemist at the University of Essex, looks at the science behind drugs in sport. Using the performance of top athletes, Cooper begins by outlining the limits of human performance. Showing the basic problems of human biochemistry, physiology, and anatomy, he looks at what stops us running faster, throwing longer, or jumping higher. Using these evidence-based arguments he shows what the body can, and cannot, do. There is much curiosity about why certain substances are used, how they are detected, and whether they truly have an effect on the body. Cooper explains how these drugs work and the challenges of testing for them, putting in to context whether the 'doping' methods of choice are worth the risk or the effort.